Effect of Smoking on Survival in patients with Squamous Cell Carcinoma of Oral Cavity - Khadeeja Khan, Javeria Ghafoor, Muhammad Immran, Muhammad Faisal Aslam, Nimrah Ishaque, Ashja Saleem, Maheen Rana, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Oral squamous cell carcinoma (OSCC) is a growing disease affecting older men and those without risk factors. It's also increasing in younger individuals. Understanding the disease's evolving patterns and risk factors is crucial for effective management. Tobacco is the primary cause, contributing to 95% of OSCC. New prevention and treatment approaches are possible with genetic markers and environmental triggers. Study Design: A cross-sectional study Place of Study: Chughtai Institute of Pathology, Lahore Study Duration: January 2022 to May 2023 Methodology: A study involving 46 patients with oral squamous cell carcinoma (OSCC) found that tobacco use significantly impacts the long-term prognoses and treatment. The patients underwent extensive surgery and received personalized adjuvant treatment. The study aimed to evaluate the impact of multimodal therapy on patient survival and quality of life. Result: The patient also exhibited the table's traits. Most patients were male. The tongue was the most affected with 26 instances (65%), whereas the buccal mucosa had 10 cases (25%) Floor of mouth (10%). It is highly probable that the mouth was involved. 24% of patients had PT1, 35% had pT2, 11% had pT3, etc. 56% of patients had pathogenic nodal stage pN0, 15% had pN1, 27% had pN2, and 2% had pN3. The median depth of invasion was 10 millimetres, with the smallest margin being six. Conclusion: The research also categorized patients based on age and tobacco consumption, revealing that smokers experience distinct psychological and functional effects. The findings could help tailor OSCC treatment to tobacco-consuming countries like Pakistan. Keywords: Squamous cell carcinoma, survival, Oral cancer, tobacco